PERANAN KOMODITAS UNGGULAN TANAMAN PANGAN TERHADAP PEMBANGUNAN EKONOMI WILAYAH PROPINSI SUMATERA BARAT - Ilham Martadona; Angelia Leovita (Diponegoro University, 2019)
The food crops sub-sector contributes the second largest to Indonesia's Gross Domestic Product (GDP), following the subsector of plantation crops. A number of food crops undergo suplus production, is expected to contribute to economic development in the region of West Sumatra Province. The purpose of this study is to analyze food crops commodities as a pre-eminent commodity in every region of West Sumatra Province and analyzing the role of each of the leading commodities to the economic development of West Sumatra Province.Location Quotient (LQ) is used to obtain competitive commodities and analysis of surplus production (SP) was used to analyze how much the role of the main commodity to economic development. The results showed the superior commodities of food crops are corn, rice paddy, and sweet potato. Main commodity of paddy rice field has the most development area in West Sumatera Province. Main commodity of corn is commodity which has the biggest role to economic development in West Sumatera Province.